IMPLEMENTASI AKAD MUSAQAH PADA SEKTOR PERTANIAN KAKAO DI DESA LEMBAH SUBUR KECAMATAN DANGIA KABUPATEN KOLAKA TIMUR SULAWESI TENGGARA - Imbar Imbar Imbar; Fitri Kumalasari; Muh Yusuf (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Lembah Subur Village is one of the villages of 12 villages in Dangia sub-district, East Kolaka district which was founded in 2002, which has a majority of farmers. Besides farmers in their own gardens, there are also farmers who work in other people's gardens. Then there is a collaboration for agricultural production based on kinship and trust of each party, and a contract that is carried out orally. So that the implementation has no legal force and there is no strong evidence that an agreement has occurred between the two parties.The formulation of the problem in this research is How is the mechanism of the agreement for the results of the cocoa farming sector in Lembah Subur Village, Dangia District, East Kolaka Regency? and how is the implementation of the musaqah contract in the cocoa farming sector in Lembah Subur Village, Dangia District, East Kolaka Regency? The objectives were to determine the mechanism of the production sharing agreement in the cocoa farming sector in Lembah Subur Village and to determine the implementation of the musaqah contract in the cocoa farming sector in Lembah Subur Village, Dangia District, East Kolaka Regency.The research method used is a descriptive qualitative approach, the research location is in Lembah Subur Village, Dangia District, East Kolaka Regency, Southeast Sulawesi. Primary data is data obtained directly from sources while secondary data comes from various sources related to this research, such as books, journals and others. Methods of data collection through observation, interviews and documentation then reduce data, present data and draw conclusions.The results showed that the agricultural production sharing agreement was made by the owner of the garden and the tenant farmers, where all the costs were borne by the owner of the garden while the tenants only took care, watered and spent their energy and time. The production sharing agreement mechanism is carried out orally with the sharing of the results based on the agreement of the two parties. The agricultural production sharing system between garden owners and tenant farmers in Lembah Subur Village is appropriate because it has fulfilled the pillars and conditions of the musaqah contract.